Leadership qualities and practices of Filipino women entrepreneurs in the wedding industry - Orosco, Farah Kharen A.; Gatchalian, Corazon Fausto (2009.)
ABSTRACT. This study focused on the women entrepreneurs in the wedding industry, particularly caterers and cake confectioners. The overriding objective of this study was to describe personal characteristics, ethical leadership practices and leadership traits of the respondents. Specifically, it aimed to determine the relationships between leadership traits and ethical leadership practices of the respondents; relationships between personal characteristics and ethical leadership practices; and to describe women entrepreneurs concept of ethical leadership.Survey data were gathered from 34 respondents using a 4-part questionnaire.Case studies were conducted on three women entrepreneurs' in the wedding industry.Over 73% mentioned that they are college graduates. They came from medium-sized families with four siblings, many of them first and second born. Majority of the respondents were engaged in entrepreneurial activities at the young age of nine years. The study revealed that most of the respondents were motivated by their parents, mothers in particular, to engage in business.Majority started catering and cake confectioners business at home in year 2000 using their own personal savings with a capital of less than P50,000.00. Most of them performed catering/confectionery sales activities with less workload on legal matters. Annual revenue was found to be less than P500,000.00 and from P501,000.00 to 1 million, respectively.Respondents ranked high in ethical leadership practices, personal leadership traits and managerial leadership traits. Description of personal characteristics vis-a-vis ethical leadership practices of the respondents ranked high in terms of the descriptor level - High Ethical Leadership. Additionally, personal characteristics were found to have significant association with ethical leadership. However, "acquired business status" was found to be dependent with ethical leadership. There were significant relationships among personal leadership traits and ethical leadership practices;managerial leadership traits and ethical leadership practices and managerial and personal leadership traits. In this study, female entrepreneurs in the cake confectioners and catering industry have high levels of ethical leadership practices and satisfactory personal and managerial leadership traits. Studies along these lines may be pursued to determine the relationships among personal characteristics, ethical leadership practices, and leadership traits of Filipino women entrepreneurs in the wedding industry.In this sense, it is imperative that local government extends its assistance to women entrepreneurs in the wedding industry through development of courses that would dwell on entrepreneurship and its legal underpinnings. This study suggests that wedding industry be categorized under "services" and not just "others" for women entrepreneurs to experience the same privileges extended to the key players of local hospitality and tourism industry.
Thesis (Master Food Service Administration)--University of the Philippines Diliman.
Keywords: Women food service employees -- Philippines -- Metro Manila; Caterers and catering -- Philippines -- Metro Manila; Businesswomen -- Philippines -- Metro Manila